Gravimetric sensors operating at 1.1 GHz based on inclined c-axis ZnO grown on textured Al electrodes - Girish Rughoobur (Nature Portfolio, 2017)
Abstract Shear mode solidly mounted resonators (SMRs) are fabricated using an inclined c-axis ZnO grown on a rough Al electrode. The roughness of the Al surface is controlled by changing the substrate temperature during the deposition process to promote the growth of inclined ZnO microcrystals. The optimum substrate temperature to obtain homogeneously inclined c-axis grains in ZnO films is achieved by depositing Al at 100 °C with a surface roughness ~9.2 nm, which caused an inclination angle of ~25° of the ZnO c-axis with respect to the surface normal. Shear mode devices with quality-factors at resonance, Q r and effective electromechanical coupling factors, $${{\boldsymbol{k}}}_{{\bf{eff}}}^{{\bf{2}}}$$ k eff 2 , as high as 180 and 3.4% are respectively measured. Mass sensitivities, S m of (4.9 ± 0.1) kHz · cm2/ng and temperature coefficient of frequency (TCF) of ~−67 ppm/K are obtained using this shear mode. The performance of the devices as viscosity sensors and biosensors is demonstrated by determining the frequency shifts of water-ethanol mixtures and detection of Rabbit immunoglobin G (IgG) whole molecule (H&L) respectively.